Beach litter dynamics on Mediterranean coasts: Distinguishing sources and pathways. Issue 2 (April 2018) - Prevenios, Michael; Zeri, Christina; Tsangaris, Catherine; Liubartseva, Svitlana; Fakiris, Elias; Papatheodorou, George
Abstract: We assessed amounts, composition and net accumulation rates every 15 days of beach macro litter (≥ 2.5 cm) on 4 Mediterranean beaches, on Corfu island, N. Ionian Sea, taking into account natural and anthropogenic drivers. Average net accumulation rate on all beaches was found 142 ± 115 N/100 m/15 d. By applying a Generalized Linear Model (GzLM) it was shown that sea transport is the dominant pathway affecting the amount and variability in beach litter loadings. Principal Component Analysis (PCA) on compositional data and indicator items discerned two more pathways of beach litter, i.e. in situ litter from beach goers and wind and/or runoff transport of litter from land. By comparing the PCA results to those from a simple item to source attribution, it is shown that regardless their source litter items arrive at beaches from various pathways. Our data provide baseline knowledge for designing monitoring strategies and for setting management targets. Highlights: Sea wave transport is the dominant pathway providing litter to beaches. PCA on beach litter specific categories revealed sources as well as pathways. Two litter pools 'aged' and 'recent' follow different spatiotemporal dynamics. Wood and fishing related items were excellent indicators for transport mechanisms. Paper and plastic pieces were excellent indicators of 'recent' and 'aged' litter respectively.